Aromaticity reversals and their effect on bonding in the low-lying electronic states of cyclooctatetraene. Issue 43 (28th October 2021) - Karadakov, Peter B.; Preston, Nicholas
Abstract : Aromaticity reversals and their effect on bonding in the low-lying electronic states of cyclooctatetraene are investigated through a visual approach which examines variations in isotropic magnetic shielding in the space surrounding the molecule. Abstract : Aromaticity reversals and their effect on chemical bonding in the low-lying electronic states of cyclooctatetraene (COT) are investigated through a visual approach which examines the variations in isotropic magnetic shielding in the space surrounding the molecule. The ground state (S0 ) of COT is shown to be strongly antiaromatic at the π-bond-shifting transition state (TS), a regular octagon of D 8h symmetry; S0 antiaromaticity decreases at the D 4h planar bond-alternating tub-to-tub ring-inversion TS but traces of it are shown to persist even at the tub-shaped D 2d local minimum geometry. The lowest triplet (T1 ) and first singlet excited (S1 ) states of COT are found to have very similar D 8h geometries and visually indistinguishable shielding distributions closely resembling that in benzene and indicating similarly high levels of aromaticity. Unexpectedly, COT diverges from its antiaromatic predecessor, cyclobutadiene, in the properties of the second singlet excited state (S2 ): In cyclobutadiene S2 is antiaromatic but in COT this state turns out to be strongly aromatic, with a shielding distribution closely following that around S2 benzene.